The honey bee pathosphere of Mongolia: European viruses in central Asia - Tsevegmid K. (2017)
© 2016 Tsevegmid et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Parasites and pathogens are apparent key factors for the detrimental health of managed European honey bee subspecies, Apis mellifera. Apicultural trade is arguably the main factor for the almost global distribution of most honey bee diseases, thereby increasing chances for multiple infestations/infections of regions, apiaries, colonies and even individual bees. This imposes difficulties to evaluate the effects of pathogens in isolation, thereby creating demand to survey remote areas. Here, we conducted the first comprehensive survey for 14 honey bee pathogens in Mongolia (N = 3 regions, N = 9 locations, N = 151 colonies), where honey bee colonies depend on humans to overwinter. In Mongolia, honey bees, Apis spp., are not native and colonies of European A. mellifera subspecies have been introduced ~60 years ago. Despite the high detection power and large sample size across Mongolian regions with beekeeping, the mite Acarapis woodi, the bacteria Melissococcus plutonius and Paenibacillus larvae, the microsporidian Nosema apis, Acute bee paralysis virus, Kashmir bee virus, Israeli acute paralysis virus and Lake Sinai virus strain 2 were not detected, suggesting that they are either very rare or absent. The mite Varroa destructor, Nosema ceranae and four viruses (Sacbrood virus, Black queen cell virus, Deformed wing virus (DWV) and Chronic bee paralysis virus) were found with different prevalence. Despite the positive correlation between the prevalence of V. destructor mites and DWV, some areas had only mites, but not DWV, which is most likely due to the exceptional isolation of apiaries (up to 600 km). Phylogenetic analyses of the detected viruses reveal their clustering and European origin, thereby supporting the role of trade for pathogen spread and the isolation of Mongolia from South-Asian countries. In conclusion, this survey reveals the distinctive honey bee pathosphere of Mongolia, which offers opportunities for exciting future research.